Composition of mixed-species bird flocks in forest fragments of southern Brazil - Brandt, Cláudia Sabrine (2014)
The present study aimed to evaluate the composition of mixed-species bird flocks in a fragmented landscape of the Atlantic Forest in southern Brazil. We recorded 117 species in 218 mixed-species flocks. The correspondence analysis showed two distinct groups of fragments according to degree of connectivity with other fragments. The percentage of original cover surrounding a sampled fragment area up to a ratio of 2.5 and 1 km was the variable that presented highest correlation with the formation of different composition of mixed-species bird flocks, followed by altitude. Based on these results, we concluded that, in landscapes with low levels of fragmentation, the composition of mixed flocks reflects the local species pool. Thus, future studies comparing composition of mixed-specie flocks should concentrate their efforts in areas where some of these variables remain constant, as for example where fragments are at similar altitudes.